The conception of work and higher education among Israeli Arab women. (2016) - Cinamon, Rachel Gali; Habayib, Halah; Ziv, Margalit
Highlights: Contextual aspects of the career development of Arab's women were explored. Results reveled arduous journey to become educated working mother. Interpersonal relations, conflicts, and resources shape their development. Abstract: The current study focuses on the conception of work and higher education among ten Israeli Arab women, enrolled in an undergraduate program of early childhood education. This qualitative study aims to explore the gap between women's career development in under-investigated cultures and career development assumptions traditionally reported in the literature. We explored the contextual aspects within Arab society that shape women's career development, as well as their own candid conceptions of their development. The content analysis of the interviews revealed various aspects of a long and arduous journey to the desired goal of becoming an educated working mother. Six domains were identified: studies, interpersonal relations, conflicts and difficulties, resources, decision-making processes, and future perceptions. Implications for practice and further research are discussed.